(untitled) (Comparative & International Education Series, 2021)
Our study collected quantitative and qualitative data sets on the attitudes and experience of 400 students from across all years of an undergraduate degree program in the Social Sciences at a large urban university in Australia. Participants were either preparing for an upcoming Study Abroad program or had recently returned from a sojourn abroad. A large-scale survey enabled the collection of contextual and demographic data of all participants while individual interviews with a sub-set of 31 participants enabled the collection of detailed and rich, qualitative data to understand the student experience of being a first generation Study Abroad student. While challenges to participation in Study Abroad programs exist for all students, this study found that the first generation students do face some specific issues, including relatively lower rates of proficiency in languages other than English and less experience in international travel compared to other students.